Who is the Real Author? - Malik, Tayyaba Gul (Pakistan Journal of Ophthalmology, 2017)
Non-arteritic anterior ischemic optic neuropathy is a vascular disease of optic nerve head. It occurs around 60 years of age and usually associated with hypertension, diabetes, hyperlipidemia and smoking. We present a case of bilateral optic disc drusen with unilateral anterior ischemic optic neuropathy in a 50 years old Asian male. He had history of transient obscuration of vision before he developed non-arteritic anterior ischemic optic neuropathy. Intra vitreal Bevacizumab was given and no improvement was seen in visual acuity after three months of follow up. KEY WORDS Optic disc drusen, transient obscuration of vision, non-arteritic anterior ischemic optic neuropathy, optic disc edema, intravitreal Bevacizumab.